Towards Molecular Design Rationalization in Branched Multi-Thiophene Semiconductors: The 2-Thienyl-Persubstituted α-Oligothiophenes - Benincori, Tiziana; Bonometti, Valentina; De Angelis, Filippo; Falciola, Luigi; Muccini, Michele; Mussini, Patrizia R.; Pilati, Tullio; Rampinini, Giovanni; Rizzo, Simona; Toffanin, Stefano; Sannicolò, Francesco (Chemistry : a European journal, 2010)
The introduction of branching in multi‐thiophene semiconductors, although granting the required solubility for processing, results in an increased molecular fluxionality and a higher level of distortion, thus hampering π conjugation. Accordingly, branched oligothiophenes require rationalization of their structure–reactivity relationships for target‐oriented design and optimization of the synthetic effort. Our current research on spiderlike oligothiophenes affords deep insight into the subject, and introduces new, easily accessible molecules with attractive functional properties. In particular, a regular series, T′XY, of five new multi‐thiophene systems, T′53, T′84, T′115, T′146, and T′177, constituted by five, eight, 11, 14, and 17 thiophene units, respectively, their longest α‐conjugated chain consisting of tri‐, tetra‐, penta‐, hexa‐, and heptathiophene moieties, respectively, has been synthesized and fully characterized from the structural, spectroscopic, and electrochemical point of view. The electronic properties of the monomers and their electropolymerization ability are discussed and rationalized as a function of their molecular structure, particularly in comparison with the series of 5‐(2,2′‐dithiophene)yl‐persubstituted α‐oligothiophenes (TXY) previously reported by us. These oligothiophenes are easily accessible materials, with promising properties for applications as active layers in multifunctional organic devices including solar cells. Branching out: A series of multi‐thiophene systems comprising 5, 8, 11, 14, and 17 thiophene units (an example of which is depicted), their longest α‐conjugated chain consisting of tri‐, tetra‐, penta‐, hexa‐, and heptathiophene moieties, respectively, has been synthesized and fully characterized from the structural, spectroscopic, and electrochemical point of view.